Optimising neonatal service provision for preterm babies born between 27 and 31 weeks gestation in England (OPTI-PREM), using national data, qualitative research and economic analysis: a study protocol - Pillay, T; Modi, N; Rivero-Arias, O; Manktelow, B; Seaton, SE; Armstrong, N; Draper, ES; Dawson, K; Paton, A; Ismail, AQT; Yang, M; Boyle, EM (BMJ Publishing Group, 2019)
INTRODUCTION: In England, for babies born at 23-26 weeks gestation, care in a neonatal intensive care unit (NICU) as opposed to a local neonatal unit (LNU) improves survival to discharge. This evidence is shaping neonatal health services. In contrast, there is no evidence to guide location of care for the next most vulnerable group (born at 27-31 weeks gestation) whose care is currently spread between 45 NICU and 84 LNU in England. This group represents 12% of preterm births in England and over onr-third of all neonatal unit care days. Compared with those born at 23-26 weeks gestation, they account for four times more admissions and twice as many National Health Service bed days/year. METHODS: In this mixed-methods study, our primary objective is to assess, for babies born at 27-31 weeks gestation and admitted to a neonatal unit in England, whether care in an NICU vs an LNU impacts on survival and key morbidities (up to age 1 year), at each gestational age in weeks. Routinely recorded data extracted from real-time, point-of-care patient management systems held in the National Neonatal Research Database, Hospital Episode Statistics and Office for National Statistics, for January 2014 to December 2018, will be analysed. Secondary objectives are to assess (1) whether differences in care provided, rather than a focus on LNU/NICU designation, drives gestation-specific outcomes, (2) where care is most cost-effective and (3) what parents' and clinicians' perspectives are on place of care, and how these could guide clinical decision-making. Our findings will be used to develop recommendations, in collaboration with national bodies, to inform clinical practice, commissioning and policy-making. The project is supported by a parent advisory panel and a study steering committee. ETHICS AND DISSEMINATION: Research ethics approval has been obtained (IRAS 212304). Dissemination will be through publication of findings and development of recommendations for care. TRIAL REGISTRATION NUMBER: NCT02994849 and ISRCTN74230187.